Strategy for action - II : strategy formulation, development, and control - Gandellini, Giorgio; Pezzi, Alberto; Venanzi, Daniela (SpringerBriefs in Business, 2013)
The innovative and unique feature of this book is that it does not contain theoretical concept that cannot be translated into practice. This second volume expands the analysis of the strategic decisions, emphasizing the importance of a sustainable competitive advantage, and proposing an integrated conceptual and operational framework (the "Strateco Dashboard"), that complements and significantly improves the recent and well-known Blue Ocean approach to strategy development. Finally, it addresses the measurement of the performance of strategy in terms of value creation, highlighting differences and similarities, as well as strengths and weaknesses, of the main metrics. Furthermore, it proposes a comprehensive and operational framework for the assessment of the financial feasibility of strategy, through the measurement of the impact of the planned strategic moves on financial needs and the evaluation of their financial sustainability.